Data for "Anion Ordering and Phase Stability Govern Optical Band Gaps in BaZrS3xSe3–3x" - Fransson, Erik; Kayastha, Prakriti; Whalley, Lucy; Erhart, Paul (Chalmers University of Technology, 2026)
This record contains data supporting the paper "Anion Ordering and Phase Stability Govern Optical Band Gaps in BaZrS3xSe3–3x.

nep.txt – neuroevolution potential (NEP) model in a format that is compatible with, e.g., GPUMD or calorine

train.xyz – reference dataset generated using density functional theory (DFT) calculations used for training the neuroevolution potential (NEP) model

control.in – example input file for FHIaims used for generating the density functional theory (DFT) reference data

PBE-*.db – database in SQLite format readable by ase containing dielectric function data generated by density functional theory (DFT) calculations carried out using VASP

PBE-composition.db – data for snapshots from molecular dynamics (MD) simulations at 300 K based on the NEP model; the configurations span the entire composition range (x=0...1)

PBE-Pnma-S0.33.db – data for snapshots from MD and Monte Carlo-MD hybrid simulations at 100, 200, and 300 K based on the NEP model; the configurations are restricted to 33% S
Keywords: Physical Sciences; Fysik